The influence of concentration and temperature on the viscoelastic properties of tomato pomace dispersions. (December 2016) - Belović, Miona; Pajić-Lijaković, Ivana; Torbica, Aleksandra; Mastilović, Jasna; Pećinar, Ilinka
Abstract: The influence of concentration and temperature on the rheological properties of tomato pomace dispersions obtained by rehydration of lyophilized and grinded tomato pomace was investigated in this paper. Examined systems comprised of different lyophilized tomato pomace concentrations (18.2, 16.7, 14.3, 12.5, 11.1, 10.0, and 9.1%) heat treated at two different temperatures (60 °C and 100 °C) during 30 min. According to microstructure analysis of the studied system, it could be simplified as the composite consisting of insoluble particles surrounded by the pectin network. The system behaves as viscoelastic solid (G′ > G″ at all angular velocities), and therefore the static modulus of elasticity, the effective modulus and the damping coefficient were determined by application of modified fractional Kelvin-Voigt model. The influence of particle concentration on the rheological properties of tomato pomace system is dominant in comparison to the content and composition of pectin solubilised in the serum. Concentrated tomato pomace dispersions are much stiffer (G′ values an order of magnitude higher) than the composite systems. Heat treatment at higher temperature (100 °C) decreases the stiffness of the system by breaking of non-covalent bonds between dispersed tomato particles and surrounding pectin network. Storage modulus as a function of the tomato pomace lyophilizate concentration was considered within three regimes (regime 1 – concentration <11.1%; regime 2 – concentration 11.1%–16.7%; regime 3 – concentration >16.7%) that could be used as the base for formulation of tomato pomace-based products with different desirable consistencies, such as sauce, ketchup and marmalade. Graphical abstract: Highlights: Structural and rheological properties of tomato pomace dispersions were studied. Modified fractional Kelvin-Voigt model was successfully applied on the system. The system behaviour is dominantly influenced by particle concentration. Heat treatment at higher temperature decreases the stiffness of the system.